Public hospital spending in England: Evidence from National Health Service administrative records - Elaine Kelly; George Stoye; Marcos Vera-Hernández (Institute for Fiscal Studies (IFS), 2015)
Health spending per capita in England has more than doubled since 1997, yet relatively little is known about how that spending is distributed across the population. This paper uses administrative National Health Service (NHS) hospital records to examine key features of public hospital spending in England. We describe how costs vary across the lifecycle, and the concentration of spending among people and over time. We find that costs per person start to increase after age 50 and escalate after age 70. Spending is highly concentrated in a small section of the population: with 32% of all hospital spending accounted for by 1% of the general population, and 18% of spending by 1% of all patients. There is persistence in spending over time with patients with high spending more likely to have spending in subsequent years, and those with zero expenditures more likely to remain out of hospital.
Keywords: H51; I10; I11; 330; Health; public spending; hospitals